2007
DOI: 10.1038/sj.jcbfm.9600456
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contribution of Nuclear Factor-κB to Cerebral Vasospasm after Experimental Subarachnoid Hemorrhage in Rabbits

Abstract: Nuclear factor-jB (NF-jB) plays a key role in inflammation, which is involved in the development of cerebral vasospasm after subarachnoid hemorrhage (SAH). In the present study, we assessed the potential role of NF-jB in regulation of cerebral vasospasm. Nuclear factor-jB DNA-binding activity was measured in cultured vascular smooth muscle cells (VSMCs) treated with hemolysate and pyrrolidine dithiocarbamate (PDTC, 80 lmol/L), an inhibitor of NF-jB. Forty-two rabbits were divided into three groups: control, SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 37 publications
(49 reference statements)
3
70
0
1
Order By: Relevance
“…Mechanisms of efficacy of MnTnHex-2-PyP in SAH will be the subject of further investigation. Evidence from the MCAO model reported above suggests that MnTnHex-2-PyP effects on NF-B activation and inflammatory gene expression may be involved in this mechanism of vasospasm progression (Zhou et al, 2007), but this remains to be tested. It is noteworthy that although not performed concurrently but examined in an identical SAH model, the effect size of MnTnHex-2-PyP exceeded that of simvastatin when treatment was begun postictus (e.g., after SAH MCA diameter increased by 24% with simvastatin versus 48% with MnTnHex-2-PyP) .…”
Section: Lipophilic Mnporphyrins In Experimental Mcao and Sah 913mentioning
confidence: 99%
“…Mechanisms of efficacy of MnTnHex-2-PyP in SAH will be the subject of further investigation. Evidence from the MCAO model reported above suggests that MnTnHex-2-PyP effects on NF-B activation and inflammatory gene expression may be involved in this mechanism of vasospasm progression (Zhou et al, 2007), but this remains to be tested. It is noteworthy that although not performed concurrently but examined in an identical SAH model, the effect size of MnTnHex-2-PyP exceeded that of simvastatin when treatment was begun postictus (e.g., after SAH MCA diameter increased by 24% with simvastatin versus 48% with MnTnHex-2-PyP) .…”
Section: Lipophilic Mnporphyrins In Experimental Mcao and Sah 913mentioning
confidence: 99%
“…The perivascular-activated monocytes after SAH have been reported as one major source of ET-1 that can cause delayed CVS (Fassbender et al, 2000). There may be a possible link of CVS to SAH-induced Ca 2 + oscillations through inflammation, because inactivation of NF-kB by pyrolidine dithiocarbamate or antisense oligonucleotids attenuates vasospasm in animal models of SAH (Ono et al, 1998;Zhou et al, 2007). In analogy to the reduction of Ca 2 + oscillation frequency and NF-kB activation, xestospongin, and thapsigargin reduced the expression of VCAM-1.…”
Section: The Role Of Ca 2 + Oscillations In Normal Physiology and Aftmentioning
confidence: 99%
“…This may result in the transmigration of T-cells and monocytes into the vessel wall (De Martin et al, 2000). In addition, both NF-kB and VCAM-1 have been shown to be involved in the pathogenesis of CVS after SAH (Kaynar et al, 2004;Polin et al, 1998;Zhou et al, 2007). The intracellular Ca 2 + concentration regulates the function of the endothelial barrier between blood and the surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated that hemolysate is associated with an increase in NF-jB-binding activity in vascular smooth muscle cells (Zhou et al 2007). In order to examine the involvement of NF-jB in ICAM-1 and MCP-1 expression, BMECs were treated with hemolysate, and the translocation of NF-jB was measured by Western blot.…”
Section: Icam-1 and Mcp-1 Expression Is Regulated By Different Transcmentioning
confidence: 97%